Hypertonic HBOC-201 Decreases Neutrophil Activation after Hemorrhagic Shock. (1st February 2014) - Rivera-Chávez, Fernando A.; Lu, Amanda; Liu, Ming-Mei; Abdalla, Adil; Minei, Joseph P.
ABSTRACT Objective: To evaluate neutrophil activation after exposure to standard HBC-201 (suspended in lactate Ringer's solution) versus HBOC-201 suspended in hypertonic 7.5% saline solution. Methods: We use plasma and tissue obtained from pigs subjected to controlled hemorrhagic shock and an ex vivo model of stimulated human whole blood. The pigs were resuscitated with the following (n = 8 per group) standard HBOC-201, or hypertonic HBOC-201. We used HTS 7.5%, Ringer's lactate as control resuscitation. Human blood was stimulated with same fluids. We measured the following neutrophil markers; IL-8, H2O2 in pig plasma, MPO in pig tissue, and H2O2, IL-8, and CD11b/CD18 in human whole blood. Results: H2O2 and IL-8 as well as tissue MPO were significantly decreased in pigs resuscitated with HT-HBOC-201 and HT 7.5%. Ex vivo experiments blood diluted with HTS and HT-HBOC-201 revealed lower expression of CD11b/CD18, H2O2, and IL-8. Blood diluted with HBOC-201 had a higher CD11b/CD18 expression than blood diluted with LR solution. Conclusion: Our in vivo and ex vivo experiments indicate that HBOC-201 suspended in hypertonic 7.5% saline solution is associated with significantly less neutrophil activation when compared to standard HBOC-201 suspended in lactate Ringer's solution.